Answer:
c
Step-by-step explanation:
because it would have many solutions
Answer:
-2^(x-2)
Step-by-step explanation:
Using differential calculus:
We know that the integral of 1/x = ln(x)
or 2x/ln(2) = log2(x), so we plug in our knowledge and chain rule to figure out that the answer to the inverse is -2^(x-2) :)
a is given to us so just plug a into the first equation:
b-3 - 3b =9
Add 3 to both sides:
b-3b=12
Combine like terms:
-2b=12
Divide by -2 to get b by itself:
b=-6
The only answer with b as -6 is the first one, (-9,-6)
Answer:
Step-by-step explanation:
4/3 = t/7
Multiply by 7 on both sides
4/3 x 7 = t
28/3 = t
Step-by-step explanation:
let d+e=2 be equation 1
let d-e=4 be equation 2
lets make d the subject in equa 1
d = 2-e equation 3
put equation 3 in 2
2-e=4
e=2-4
e=-2
put e=-2 in equa 1
d-2=2
d=4
e is -2 and d is 4